Guided Discovery Learning Berbasis Indigenous Knowledge untuk Melatih Keterampilan Berpikir Kritis Siswa - Anjelica Octavia Arung; Farah Erika; Mukhamad Nurhadi (Universitas Indraprasta PGRI Jakarta, 2022)
Critical thinking skills are high-level thinking skills that must be developed in schools. These skills need to be trained through the use of learning models that bring students closer to real experiences in the surrounding environment, so that students become more active and able to think critically, one of which is applying the indigenous knowledge-based GDL model. This study aims to train students' critical thinking skills through the application of the indigenous knowledge-based GDL model. The subjects of this study were 108 students consisting of class XI IPA 4, XI IPA 5, and XI IPA 6 SMA Negeri 5 Samarinda for the academic year 2020/2021 which were selected using a purposive sampling technique. This research is classified as quantitative research with a pre-experimental research design type one-group pretest-posttest design. The critical thinking skills test instrument was 5 essay questions composed of 5 indicators. The results of the analysis of critical thinking skills show that the average critical thinking skills of class XI science students at SMAN 5 Samarinda were in the medium category with an n-gain of 0.53; the mean effect size of 5.17 belongs to the large category; statistical test results (? = 5%) which showed a significant increase in critical thinking skills after the application of the indigenous knowledge-based GDL model. Based on this, it can be said that the indigenous knowledge-based GDL model is effectively used to train students' critical thinking skills.